Synthesis of some bis(styryl) containing coumarin ring from substituted 3-acetyl-4-methylcoumarin - Nguyen, Thanh Ngoc; Vu Minh Tan, (Vietnam Journal of Science and Technology, 2025)
Three substituted 3-acetyl-4-methylcoumarin have been synthesized by reaction of substituted o-hydroxyacetophenone with ethyl acetoacetate and sodium acetate as a catalyst (Pechmann reaction). Then, this derivatives reaction with aromatic aldehyde received eleven new substituted 3-((E)-arylprop-2-enoyl)-4-((E)-styryl)coumarin. The structure of compounds confirmed data from IR, NMR, and MS spectroscopy. Furthermore, using the HyperChem Release 8.0 software, quantum chemical calculations revealed that the charge density of the carbon atoms present in the 4-methyl and 3-acetyl groups in the α-pyrone ring are nearly identical. Based on this, it can be hypothesized that chemical reactions can take place in two steps. Firstly, step 1 involves the Claisen-Schmidt condensation reaction of the 3-COCH3 group with the aromatic aldehyde, resulting in the formation of an α,β-unsaturated ketone intermediate. Subsequently, in step 2, the 4-CH3 group present in the α,β-unsaturated ketone intermediate reacts with an aromatic aldehyde, leading to the formation of bis(styryl).